Synthetically Important Alkali-Metal Utility Amides: Lithium, Sodium, and Potassium Hexamethyldisilazides, Diisopropylamides, and Tetramethylpiperidides - Mulvey, Robert E.; Robertson, Stuart D. (Angewandte Chemie International Edition, 2013)
Most synthetic chemists will have at some point utilized a sterically demanding secondary amide (R2N−). The three most important examples, lithium 1,1,1,3,3,3‐hexamethyldisilazide (LiHMDS), lithium diisopropylamide (LiDA), and lithium 2,2,6,6‐tetramethylpiperidide (LiTMP)—the “utility amides”—have long been indispensible particularly for lithiation (Li‐H exchange) reactions. Like organolithium compounds, they exhibit aggregation phenomena and strong Lewis acidity, and thus appear in distinct forms depending on the solvents employed. The structural chemistry of these compounds as well as their sodium and potassium congeners are described in the absence or in the presence of the most synthetically significant donor solvents tetrahydrofuran (THF) and N,N,N’,N’‐tetramethylethylenediamine (TMEDA) or closely related solvents. Examples of hetero‐alkali‐metal amides, an increasingly important composition because of the recent escalation of interest in mixed‐metal synergic effects, are also included. Essential utilities: The Li, Na, and K salts of 1,1,1,3,3,3‐hexamethyldisilazide (HMDS, red), diisopropylamide (DA, green), and 2,2,6,6‐tetramethylpiperidide (TMP, blue) constitute one of the most synthetically important classes of compounds. In this Review, these bulky secondary amides are considered collectively, and their effectiveness as reagents discussed on the basis of their solution behavior and solid‐state structures.